The Role of Waste Banks in Integrating Social and Business Activities for Community Income Improvement - Harahap, Muhammad Ade Kurnia; Muhamad, Lili Fadli; Suherlan (Tirakat: Jurnal Terobosan Peduli Masyarakat, 2024)
Waste banks are an innovative solution for integrating social and business activities to improve community income while addressing environmental issues. This study is a literature review using a qualitative approach aimed at contributing to the community service literature. Data were sourced from Google Scholar covering the period from 2014 to 2024. From 25 articles found, 15 articles were selected based on strict relevance and quality criteria. Descriptive analysis shows that waste banks can improve community income through the management of economically valuable waste while promoting environmental awareness and community empowerment. Case studies such as the Malang Waste Bank, Gemah Ripah Waste Bank in Bantul, and Srikandi Waste Bank in Madiun show positive impacts on both social and economic aspects, including women's empowerment and job creation. However, the success of waste banks is heavily influenced by community participation, innovation, and ongoing policy support. This study recommends strengthening technology, strategic partnerships, and government incentives as steps to improve the effectiveness and sustainability of waste banks in the future.